Bentuk-Bentuk Ketidakpatuhan Aturan Akademik oleh Mahasiswa Kedokteran dan Implikasinya terhadap Profesionalisme: Sebuah Tinjauan Literatur - Aprilly Adlina Chalida; Vira Kamalia Niswah; Asep Sukohar; Septia Eva Lusina (CV. Jasa Sukses Abadi, 2026)
Professionalism is a fundamental value in medical education, encompassing integrity, responsibility, and adherence to academic regulations. However, medical students often encounter ethical dilemmas when personal values, social pressures, or academic demands trigger non-compliance with these rules. Such misconduct reflects challenges in developing a professional identity grounded in ethical integrity. This article presents a literature review of national and international studies published between 2020 until 2025 examining the relationship between medical ethics education, professionalism, and academic rule violations. The aim is to analyze ethical dilemmas arising from academic misconduct among medical students and to identify how ethical reflection and professionalism learning can be strengthened. The review indicates that academic dishonesty remains prevalent in various forms, including exam cheating, plagiarism, data and documentation falsification, attendance manipulation, and dishonesty in clinical practice. Contributing factors include academic pressure, heavy workload, collectivistic cultural norms, peer influence, previous cheating experiences, stress, and low moral reasoning. Dishonesty, particularly in clinical settings, can disrupt learning processes and jeopardize patient safety. Such behaviors also reflect a failure to meet the first competency area of the 2019 National Standard of Indonesian Medical Doctor Education (SNPPDI) and contradict the foundational principles of the 2012 Indonesian Code of Medical Ethics (KODEKI). Recommended strategies to address these issues include continuous ethics education, positive role modeling, clear professionalism assessment systems, psychological support, and consistent enforcement of sanctions.